Comparative analysis of iatrogenic injury of biliary tract in laparotomic and laparoscopic cholecystectomy - FORTUNATO,André Augusto (2014)
BACKGROUND: Iatrogenic injury to the bile ducts is the most feared complication of cholecystectomy and several are the possibilities to occur. AIM: To compare the cases of iatrogenic lesions of the biliary tract occurring in conventional and laparoscopic cholecystectomy, assessing the likely causal factors, complications and postoperative follow-up. METHODS: Retrospective cohort study with analysis of records of patients undergoing conventional and laparoscopic cholecystectomy. All the patients were analyzed in two years. The only criterion for inclusion was to be operative bile duct injury, regardless of location or time of diagnosis. There were no exclusion criteria. Epidemiological data of patients, time of diagnosis of the lesion and its location were analyzed. RESULTS: Total of 515 patients with gallstones was operated, 320 (62.1 %) by laparotomy cholecystectomy and 195 by laparoscopic approach. The age of patients with bile duct injury ranged from 29-70 years. Among those who underwent laparotomy cholecystectomy, four cases were diagnosed (1.25 %) with lesions, corresponding to 0.77 % of the total patients. No patient had iatrogenic interventions with laparoscopic surgery. CONCLUSION: Laparoscopic cholecystectomy compared to laparotomy, had a lower rate of bile duct injury.